Corrections to “Pest Identification Based on Fusion of Self-Attention With ResNet” - SK Mahmudul Hassan; Arnab Kumar Maji (IEEE Access)
Presents corrections to the paper, Corrections to “Pest Identification Based on Fusion of Self-Attention With ResNet”.